Flexible Organic Photovoltaics with Colorful Semi-Transparent Metal/Dielectric/Metal Top Electrode. (4th June 2021) - Kim, Jae Won; Yuk, Dohun; Lee, Woojin; Rasool, Shafket; Kim, Jin Young
Abstract : Organic solar cells (OSCs) have the advantages of a semi-transparent thin film, and of changing colors through controlling optical energy bandgap of organic semiconducting materials. In addition, the flexible OSCs can also be fabricated to be applied in multiple applications such as film-type or foldable solar cells. Here, we have fabricated flexible semi-transparent organic solar cells (STOSCs) with high transparency accompanying highly vivid red, green, and blue colors. To gain high transparency of STOSCs, we employed Fabry-Pérot etalon-type electrodes. An antimony oxide (Sb2 O3 ) cavity layer was introduced between two thin silver layers. By adjusting the thickness of Sb2 O3 from 45 nm to 100 nm, vivid colors of red, green, and blue semi-transparent top electrodes were achieved. Besides, selecting well-matched photoactive layers for each color, a less drop of short-circuit current density (Jsc ) has been observed. Finally, we obtained high maximum transmittance of 22.52%, 30.10%, and 22.13%, with a power conversion efficiency of 9.16%, 9.85%, and 12.64% for red, green, and blue STOSCs, respectively. Likewise, a power conversion efficiency of 5.75% was achieved with a green-colored large area sub-module.